Public health importance of Rattus norvegicus as paratenic host to Toxocara canis (Ascaroidea, Nematoda) in São Paulo county, SP, Brazil - Chieffi, Pedro Paulo (1981)
Antibodies against 'I'oxocara. canis were investigated through passive hemagglutination test in the serum of 121 specimens of Rattu» norvegicus captured in São Paulo county, state of São Paulo, Brazil. Titers of 1 :20 or higher were found in 23.2% of the specimens. The possibility of this species being a paratenic host to T. canis is suggested.